Half‐dose photodynamic therapy followed by diode micropulse laser therapy as treatment for chronic central serous chorioretinopathy: evaluation of a prospective treatment protocol. (15th December 2015) - Breukink, Myrte B.; Mohr, Jacqueline K.; Ossewaarde‐van Norel, Annette; den Hollander, Anneke I.; Keunen, Jan E.E.; Hoyng, Carel B.; Boon, Camiel J.F.
Abstract: Purpose: To evaluate the outcome of a prospective protocol for the treatment of chronic central serous chorioretinopathy (CSC). Methods: Interventional prospective case series in 59 eyes (59 patients) with active chronic CSC. All patients were first treated with indocyanine green angiography (ICGA)‐guided half‐dose photodynamic therapy (PDT). In case of persistent serous subretinal fluid (SRF) after a follow‐up period of at least 6 weeks, ICGA‐guided PDT was repeated. If the SRF persisted after two PDT treatments, additional ICGA‐guided high‐density subthreshold diode micropulse laser (HSML) therapy was performed. Clinical evaluation included best‐corrected visual acuity (BCVA), fundoscopy, OCT, fundus autofluorescence, fluorescein angiography and ICGA. Results: After a single PDT treatment, complete resolution of SRF was seen in 37 of 59 eyes. Of the 22 eyes with no complete resolution of SRF, 19 eyes received a second PDT treatment, after which seven eyes of the 19 eyes showed a complete resolution of SRF. Ten eyes underwent HSML, of which one eye had complete resolution of SRF within 7 weeks. At final follow‐up a complete resolution of SRF was present in 80% of all eyes. The mean BCVA improved from 0.28 logMAR at baseline to 0.16 logMAR at final follow‐up. Improvement of BCVA was highest after the first treatment (−0.12 logMAR, p < 0.001). Conclusions: The proposed treatment strategy using half‐dose PDT and HSML in active chronic CSC resulted in an anatomical success rate of 80%. The first half‐dose PDT treatment has the highest likelihood of a favourable treatment response on OCT and BCVA increase.